Genetic relationships among improved cassava accessions and landraces for resistance to the cassava mosaic disease - Lokko, Y.; Dixon, A.G.O.; Offei, S.K.; Danquah, E.Y. (Journal of Food, Agriculture and Environment, 2009)
This study was conducted to determine the genetic relationships among 21 accessions of cassava (Manihot esculenta), with varying levels of resistance to cassava mosaic disease (CMD), based on their phenotypic response to the disease. The accessions were ranked according to their area under the disease progress curve (AUDPC). Hierarchical cluster analysis based on Ward's linkage method separated the accessions into three major groups and the susceptible clones were distinct from the resistant accessions. Further analysis using K-means defined four groups which were similar to the groupings by the hierarchical method, but the susceptible landrace TME 117 was distinct from the other susceptible accessions. Principal component analysis showed that there was considerable amount of variation and the first three components accounted for 78.87% of the total variation in the accessions. A scatter-plot of the scores of the first and second principal components for responses to CMD showed that, generally, the resistant accessions were different from the susceptible accessions and the most susceptible landrace TME 117 formed a single member group distinct from the other susceptible groups. The large amount of variation implies that using any combination of resistant accessions to recombine different favorable alleles will not reduce the overall diversity of the breeding population.
Keywords: Area under the disease progress curve (AUDPC); Cassava mosaic disease; Genetic relationships; Phenotypic response; Virus resistance level